Estudio de los grupos taxonómicos de las papas silvestres - Cardenas, Martin (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The genus Solanum, with more than 2000 species, is subdivided into the sub-genera Pachystemonum and Leptostemonum. In the former there are five sections, one of which, Tuberarium, includes the tuber forming species of potatoes Basarthrum and Hyperba-sarthrum dare its two sub-sections and the potato properly belongs to the latter.